Proposta de unidades de paisagem para o Campus da UFSM - Rodrigues, Joane Iop (2023)
The Universidade Federal Santa Maria (UFSM) was created in 1960 and followed the precepts of the modernist style, both in architecture and urbanism. In view of the extension of UFSM and its relevance as a higher education institution in the center of the state of Rio Grande do Sul, recognition and understanding of its physical space proved to be important. Since understanding the physical evolution of the university can benefit the installation of future facilities and influence decision-making. Therefore, the objective of this work was to propose Landscape Units for the UFSM headquarters campus, based on analyzes of its land use. Proposing as a methodology the preparation and organization of relevant qualitative and quantitative data, adapting the concept of the Landscape Law in France, based on knowing, evaluating, proposing and understanding. The characteristics to be analyzed were determined and were created thematic maps, tables and graphs of the data for better understanding. Then, land use analyzes can be developed across the entire campus, with built areas and numerical data from the university. After the analyses, the result was the proposal for the 6 Landscape Units defined for the UFSM campus: Historical, Expansion, Transition, Cultural, Technological and Rural. With the units in the center of the campus more urbanized and the others in the surroundings, towards the ends, more rural. Finally, it can be seen that each UP had well-defined characteristics that characterize the UFSM campus. This suggests that the university has developed and is clearly configured, yet the importance of stipulating and following physical planning is highlighted.